2020
DOI: 10.21873/invivo.11978
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Pinus halepensis Bark Extract and Nicotine on Cigarette Smoke-induced Oxidative Stress in Keratinocytes

Abstract: Background/Aim: Cigarette smoke (CS) is a major environmental health threat. The oxidative stress induced by CS on keratinocytes and the possible protective effect of nicotine, its receptor inhibitors, and Pinus halepensis bark extract in relation to known antioxidants were investigated. Materials and Methods: Primary mouse keratinocytes were exposed to cigarette smoke in the presence and absence of Pinus halepensis bark extract (1 μg/ml), rutin (50 μΜ) and ascorbic acid (250 μΜ), nicotine (1 μM) with or witho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Pinus is a well‐known source of antioxidants, mainly phenolic compounds 24 . Lately, the antimicrobial, antidiabetic, anti‐inflammatory, and cytotoxic properties of P. halepensis have been reported 25–28 . To the best of our knowledge, P. halepensis bark extract has not been studied before with prostate cancer or prostate cancer PDT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pinus is a well‐known source of antioxidants, mainly phenolic compounds 24 . Lately, the antimicrobial, antidiabetic, anti‐inflammatory, and cytotoxic properties of P. halepensis have been reported 25–28 . To the best of our knowledge, P. halepensis bark extract has not been studied before with prostate cancer or prostate cancer PDT.…”
Section: Discussionmentioning
confidence: 99%
“…24 Lately, the antimicrobial, antidiabetic, anti-inflammatory, and cytotoxic properties of P. halepensis have been reported. [25][26][27][28] To the best of our knowledge, P. halepensis bark extract has not been studied before with prostate cancer or prostate cancer PDT. Using a natural antioxidant agent derived from renewable natural biomass as a phytopharmaceutical for prostate cancer or as a promoter of PDT efficacy in prostate cancer would be an eco-friendly and sustainable approach.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a previous study demonstrated that oral ingestion of Pycnogenol ® protected against skin damage induced by UV irradiation, modulated skin pigmentation and enhanced skin barrier function and extracellular matrix homeostasis ( 33 ). In addition, in 2020, Pavlou et al ( 34 ) reported that the bark extract of Aleppo pine ( Pinus halepensis ) protected keratinocytes against cigarette smoke-induced oxidative stress. Of note, a recent study reported that Pinus thunbergii extract ameliorated lipopolysaccharide-induced acute inflammatory responses by regulating oxidative stress ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…We prepared CSE using Longfeng Chengxiang cigarettes (carbon monoxide, 14 mg; nicotine, 1.2 mg; tar, 13 mg; Chongqing, China) as previously described [26][27][28][29][30] . Briefly, the steps are as follows: the smoke from the combustion of one cigarette was dissolved into 1 ml of DMEM/F12 using a modified 50-ml syringe as an actuating device.…”
Section: Preparation Of Cigarette Smoke Extract (Cse)mentioning
confidence: 99%